On representation by exit laws for some Bochner subordinated semigroups - Hmissi, Mohamed; Mejri, Hassen (Annales Mathematicae Silesianae, 2008)
This paper is devoted to the integral representation of potentials by exit laws in the framework of sub-Markovian semigroups of kernels acting on L2(m). We mainly investigate subordinated semigroups in Bochner sense by means of subordinators with complete Bernstein functions. As application, we give a representation for the original semigroup.